2022
DOI: 10.3390/pharmaceutics14050905
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of a Phytomedicinal Flavonoid in Biocompatible Surface-Modified Chylomicron Mimic Nanovesicles with Improved Oral Bioavailability and Virucidal Activity: Molecular Modeling and Pharmacodynamic Studies

Abstract: Morin hydrate (MH) is a widely-used Asian phytomedicinal flavonoid with a wide range of reported therapeutic activities. However, MH has limited oral bioavailability due to its low aqueous solubility and intestinal permeability, which in turn hinders its potential antiviral activity. The study reported herein was designed to encapsulate MH in polyethyleneglycolated (PEGylated) chylomicrons (PCMs) and to boost its antiviral activity and biological availability for oral administration using a rat experimental mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Also the statistical analysis revealed that doubling the EA amount from 15 mg to 30 mg resulted in a significant negative impact on the EE% ( p = 0.001). Higher amount of EA predispose to the introduction of more pores within the vesicular structure rendering it more leaky, additionally, the fluidity of the bilayer may be also increased as a consequence of the incorporation of higher amount of EA, subsequently a decline in EE% values could be noticed (Zakaria et al., 2022a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also the statistical analysis revealed that doubling the EA amount from 15 mg to 30 mg resulted in a significant negative impact on the EE% ( p = 0.001). Higher amount of EA predispose to the introduction of more pores within the vesicular structure rendering it more leaky, additionally, the fluidity of the bilayer may be also increased as a consequence of the incorporation of higher amount of EA, subsequently a decline in EE% values could be noticed (Zakaria et al., 2022a ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the surface active nature of Brij augmented in lowering the interfacial tension of the system, thus increasing its stability and resulted in formation of vesicles of lower PS. In contrary, all these effects will be diminished on using lower amounts of EA and consequently led to enlargement in PS (Abdelbary and AbouGhaly, 2015 ; Zakaria et al., 2022a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the reported method ( Zakaria et al, 2022 ), a thin film hydration technique was used for drug-emulsome incorporation with a slight alteration. Therefore, several atorvastatin-loaded emulsome (ATO-EMLs) formulae were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro dissolution experiment was carried out on three separate optimized drug-loaded formulations by modifying previously published methods [ 42 , 43 , 44 , 45 , 46 ]. Drug-loaded suspensions (15 mL) were contained in a cellulose membrane dialysis tubing with a molecular weight cut-off of 14,000 Da (D9402-100FT, Sigma Aldrich, St. Louis, MO, USA) and placed into lidded glass baths containing 500 mL PBS.…”
Section: Methodsmentioning
confidence: 99%